<meta http-equiv="refresh" content="1; url=/nojavascript/"> Polar to Rectangular Conversions ( Study Aids ) | Trigonometry | CK-12 Foundation
Dismiss
Skip Navigation

Polar to Rectangular Conversions

%
Best Score
Practice Polar to Rectangular Conversions
Practice
Best Score
%
Practice Now
Polar Graph Conversions
 0  0  0

Feel free to modify and personalize this study guide by clicking “Customize.”

Vocabulary

Explain how to graph rectangular coordinates: _______________________________________________________________________

Explain how to graph  polar coordinates:

_______________________________________________________________________

Polar to Rectangular Conversion

We can use trigonometry to convert from polar coordinates to rectangular coordinates.

Complete the coordinate conversion equations:

x = _________________                y =_________________

r^2 =_________________                tan\theta =_________________

.

Given the following polar coordinates, find the corresponding rectangular coordinates of the points:

  1. (3, \frac{\pi}{3})
  2. (2, \frac{3\pi}{2})
  3. (5, \frac{\pi}{4})

Write each polar equation in rectangular form:

  1. r=4\cos \theta
  2. r=10\sin \theta
  3. r=5\csc \theta

.

Click here for answers.

.

Rectangular to Polar Conversion

To convert from rectangular to polar coodinates, we use the Pythagorean Theorem and the Arctangent function.

Note: The Arctangent function only calculates angles in the first and fourth quadrants so \pi radians must be added to the value of \theta for all points with rectangular coordinates in the second and third quadrants.

.

Write the following points, given in rectangular form, in polar form using radians where0\leq \theta \leq 2\pi .

Remember: There are many possible polar coordinates!

  1. (5,3)
  2. (-2,4)
  3. (-7,1)
Click here for answers.
.

For each equation, convert the rectangular equation to polar form.

Hint: Use the equations x = r \cos \theta and y = r \sin \theta.

  1. 2x-y=6
  2. 3x+4y=2
  3. (x+2)^2+y^2=4
  4. (x+5)^2+(y-1)^2=26
  5. x^2+(y-6)^2=36
  6. x^2+(y+2)^2=4
Click here for answers.

Image Attributions

Reviews

Email Verified
Well done! You've successfully verified the email address .
OK
Please wait...
Please wait...

Original text